2002
DOI: 10.1007/s00381-002-0614-z
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission tomography following posterior fossa surgery in patients with and without mutism

Abstract: SPECT findings are not specific enough to explain how cerebellar mutism occurs. Clinical signs of brain stem involvement seem to be a significant risk factor in the development of cerebellar mutism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…63 Multiple studies have supported the theory of cerebellocerebral diaschisis using different imaging techniques that revealed decreased blood flow, metabolic action, and function within supratentorial structures that play a crucial role in speech production, such as the thalami, inferior frontal gyrus, and temporal lobe. 26,34,63,65,83 In almost every case the abnormal findings returned to normal when mutism resolved.…”
Section: Pathophysiologymentioning
confidence: 93%
See 3 more Smart Citations
“…63 Multiple studies have supported the theory of cerebellocerebral diaschisis using different imaging techniques that revealed decreased blood flow, metabolic action, and function within supratentorial structures that play a crucial role in speech production, such as the thalami, inferior frontal gyrus, and temporal lobe. 26,34,63,65,83 In almost every case the abnormal findings returned to normal when mutism resolved.…”
Section: Pathophysiologymentioning
confidence: 93%
“…Blood flow returned to normal when mutism resolved. Later 26 Erşahin and colleagues reported on 1 patient with right cerebellar hemisphere hypoperfusion. Sagiuchi et al 83 reported a case of CM in a 4-year-old boy with atrophy of both cerebellar hemispheres, predominately the right hemisphere, on MRI and circulatory disturbance in both hemispheres secondary to tumor resection in SPECT scans.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Single photon emission computed tomography (SPECT) revealed inconsistent fi ndings of local hypoperfusion in mute patients after posterior fossa surgery. Various MRI fi ndings were suggestive of ischemia, edema, and structural damage of midline structures as contributing factors (Pollack et al 1995 ;Ersahin et al 2002 ). Since younger children are far more prone to develop CMS after posterior fossa surgery than older children and younger age is also associated with less favorable outcome, developmental factors -such as neuronal lesion due to incompletely myelinated pathways -have been hypothesized to play a role as well (Ronning et al 2005 ).…”
Section: Posterior Fossa Syndrome/ Cerebellocerebral Diaschisismentioning
confidence: 99%